Performance of constant envelope OFDM system with nonlinear power amplifier - Qingbo WANG (Dianxin kexue)
Orthogonal frequency division multiplexing technology is widely used in wireless communication system due to its high spectral efficiency and good resistance ability to frequency selective fading.But it has high peak-to-average power ratio.Therefore,OFDM system needs large input power back-off to avoid signal distortion when using nonlinear power amplifier.In order to study the performance of the system under the condition of nonlinear power amplifier,the implementation of constant envelope OFDM was analyzed.Taking bit error rate as an index,the performance comparison between CE-OFDM system and OFDM system using traditional iterative limiting filter PAPR suppression technology were given under additive white Gaussian noise channel and multipath fading channel.